Analysis of unstable CT signs of hyperacute hypertensive cerebral hemorrhage combined with leukoaraiosis - WANG Wei; CHONG Li⁃juan; YU Miao; MENG Yan⁃kai; XU Kai (Chinese Journal of Contemporary Neurology and Neurosurgery, 2022)
Objective To analyze the imaging data of patients with hyperacute hypertensive cerebral hemorrhage with leukoaraiosis (LA), and to evaluate the possibility of unstable CT signs of hematoma as a predictor of hematoma enlargement risk. Methods The imaging data of 95 patients who were admitted to the Department of Emergency of The Affiliated Hospital of Xuzhou Medical University from March to April, 2021 and underwent head CT scan within 6 h of onset were collected, and hematoma volume was obtained by ITK ⁃SNAP software. Unstable CT signs of hematoma including irregular shape sign, mixed density sign, black hole sign, swirl sign, satellite sign, island sign and liquid⁃liquid level sign were recorded. The severity of LA was assessed by the Blennow scale. Univariate and multivariate stepwise Logistic regression analysis were used to screen the risk factors of large volume cerebral hemorrhage (≥30ml). Results According to the hematoma volume of cerebral hemorrhage, 95 cases were divided into＜30ml group (n=53) and ≥30ml group (n=42). Logistic regression analysis showed that severe LA was a risk factor for large volume hematoma in cerebral hemorrhage (OR=6.222, 95%CI: 2.506-15.452; P=0.000). CT showed that the proportions of irregular shape sign (χ2=17.599, P=0.000), mixed density sign (χ2=5.644, P=0.018), black hole sign (χ2=23.161, P=0.000), swirl sign (χ2=26.128, P=0.000), satellite sign (χ2=25.148, P=0.000), island sign (χ2=20.575, P=0.000), ≥2 combined signs (χ2=23.245, P=0.000) and ≥3 combined signs (χ2=58.902, P=0.000) were higher in the hematoma volume ≥30ml group than those in＜30ml group. Severe LA (grade Ⅱ and Ⅲ) group (n=50) showed irregular shape sign (χ2=5.502, P=0.019), black hole sign (χ2=10.715, P=0.001), swirl sign (χ2=7.336, P=0.007), satellite sign (χ2=4.467, P=0.035), island sign (χ2=19.961, P=0.000), ≥2 combined signs (χ2=12.684, P=0.000) and ≥3 combined signs (χ2=17.593, P=0.000) were higher than those in non⁃severe (non and grade Ⅰ) group (n=45). Conclusions Severe LA is an important risk factor for hematoma volume expansion (≥30ml) in hyperacute hypertensive cerebral hemorrhage. The positive rates of unstable CT signs of hematoma in acute stage are higher, suggesting that this indicator can be used as a risk predictor for hematoma expansion after cerebral hemorrhage.